Estimation Of Low Birth Weight Risk In Indonesia: What Is The Most Appropriate Intervention? - Reinpal Falefi; Nofi Susanti; Susilawati Susilawati; Hikmat Zakky Almubaraq (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: The prevalence of low birth weight (LBW) in the world (20%) and in Indonesia is still high (12.4%). The importance of efforts to reduce the incidence of LBW is written in the global nutrition targets for 2025. Methods: The study design in this study was quantitative using the data set 'Indonesian Demographic and Health Survey (IDHS) of 2017. The samples included in the research process were 13,269 samples with probability proportional to size (PPS) sampling technique. The research instrument was based on a modified DHS VII questionnaire. Data were analyzed by chi-square test, binary logistic regression, and Receiver Operating Characteristics (ROC). Results: The prevalence of LBW in Indonesia is 7% [95% CI: 6.6, 7.5]. The final model for determining low birth weight after controlling for confounding was gemelli P<0.001 [OR: 22,428; 95% CI: 14,145, 35,561], history of pregnancy complications P<0.001 [OR: 1,906; 95% CI: 1.569, 2.315], education level P=0.002 [OR: 1.581; 95% CI: 1.180, 2.117], economic status P<0.001 [OR: 1.509; 95% CI: 1.225, 1.859], and gestational interval P=0.016 [OR: 1.401; 95% CI: 1,066, 1,842]. The minimum probability of the prediction model is 2.8%-80.5% [AUC = 0.638; Sensitivity = 0.074; Specificity = 0.996]. Conclusion: Diagnostic performance with ROC evaluation on a predictive model of LBW determinant has very high specificity power. Mothers with gemelli status need to be the focus to reduce the risk of low birth weight.